Phenology and Ripening of Vitis vinifera L. and Vitis labrusca L. Varieties in the Maritime Climate of Samsun in Turkey’s Black Sea Region - Köse, B. (South African Journal of Enology and Viticulture, 2016)
Heavy rainfall in Turkey’s northern Black Sea Region in spring and autumn, combined with insufficient sunshine during the vegetation period, results in poor ripening of European grape (Vitis vinifera L.) cultivars. Compared to other coastal provinces in the Central and Eastern Black Sea Region, Samsun receives relatively little rainfall. This study evaluated the adaptation of Vitis vinifera L. and Vitis labrusca L. grapes to Samsun by examining the phenology and ripening characteristics of these cultivars in 2010 and 2011 and calculating climatic indices using long-term data for Samsun in order to assess the potential for viticulture in the area. The following climatic characteristics were identified: annual sunshine duration, 1 836 hours; Branas Heliothermic Index (BHI), 3.0; Hydrothermic Index (HyI), 4 053.7°C mm; Winkler Index (WI growing degree days) 1 832/Region III “Warm”; and Huglin Index (HI) 1 978°C/HI-1 “Temperate”. Phenological cycles (budburst to harvest) varied between 120 and 176 days, with Trakya Ä°lkeren and Yalova Ä°ncisi the most precocious varieties and Favli the latest variety in both years. Heat summation requirements ranged from 1 210 to 1 844 GDD, with Trakya Ä°lkeren requiring the least and Narince the most heat summation. Total soluble solid (TSS) values ranged from 15.1 °Brix (Trakya Ä°lkeren) to 21.4 °Brix (Labrusca). Although Favli was the last to ripen, the TSS value for this variety was only 17.1%. These findings indicate that, with the exception of Favli, all the varieties examined are capable of maturing under the climatic conditions in the study area, suggesting that the coastal areas of Samsun province are suitable for early and mid-season Vitis vinifera L. grape viticulture.